Effects of mechanical and enzymatic pretreatments on extraction of polyphenols from blackberry fruits - Soto Retana, Marvin (2016)
This study evaluated the effects of mechanical and enzymatic pretreatments on the extraction of anthocyanins and ellagitannins from blackberries. Continuous pressing yielded significantly higher turbidity values and content of anthocyanins and ellagitannins (P < 0.05) compared with discontinuous pressing. The use of enzymatic pretreatment also significantly increased the extraction of polyphenolic compounds (P < 0.05), in particular that of total ellagitannins, on average from 437 to 982 mg ellagic acid equivalents/100 g (dry basis) when using discontinuous pressing. When microfiltration was used, the content of ellagitannins and anthocyanins was found to be similar in both feed and permeate when discontinuous press was used to extract the juice, but a significant decrease of 34% (dry basis) was found in the concentration of ellagitannins when continuous pressing was used (P < 0.05). These results should be useful for future efforts to increase the extraction of polyphenolic compounds from fruits and vegetables.